Reading the Ovidian heroine : Metamorphoses commentaries, 1100-1618 - McKinley, Kathryn L. (Mnemosyne, Supplements, 2001)
This study investigates the reception of Ovid's heroines in Metamorphoses commentaries written between 1100 and 1618. The Ovidian heroine offers a telling window onto medieval and early modern clerical constructions of gender and selfhood. In the context of classical representations of the feminine, the book examines Ovid's engagement of the heroine to explore problems of intentionality. The second part of the study presents commentaries by such clerics as William of Orléans, the \'Vulgate\' commentator, Thomas Walsingham, and Raphael Regius, illustrating the reception of the Ovidian heroine in medieval France and England as well as in Renaissance Italy and Germany. The works analyzed here show that clerical readings of the feminine in Ovid reflect greater heterogeneity than is commonly alleged. Both moralizing summaries and Latin editions used as schooltexts are discussed.